Lyophilization of ASFV vaccine candidate ASFV-G-ΔI177L offers long term stability - Nallely Espinoza; Edward Spinard; Ayushi Rai; Elizabeth Ramirez-Medina; Alyssa Valladares; Amanda Meyers; Manuel V. Borca; Douglas P. Gladue (Scientific Reports)
Abstract For over a century African swine fever (ASF) has been causing outbreaks leading to devastating losses for the swine industry. The current pandemic of ASF has shown no signs of stopping and continues to spread causing outbreaks in additional countries. Currently control relies mostly on culling infected farms, and strict biosecurity procedures. Recently a vaccine, ASFV-G-ΔI177L was approved for use in Vietnam. In this study we evaluate the long-term stability of lyophilized ASFV-G-ΔI177L. Understanding the stability of different formulations of vaccines is information necessary for deployment of vaccines to ASF outbreak areas, particularly those that do not have a reliable well established cold chain to ensure conservation of vaccine quality. In this report, we determined that ASFV-G-ΔI177L, when lyophilized under specific conditions, is stable for up to one year at 4 °C, with similar vaccine titers after storage. Next-generation sequencing analysis also determined that lyophilization and long-term storage under these conditions had no effect on the genome of ASFV as the genome remained genetically identical to the original non-lyophilized form.